Strategi Penciutan PT Garuda Indonesia Tbk Dalam Menghadapi Kesulitan Keuangan - Kintan Rachmi Satyodriyani; Hesti Restarani; Popy Rufaidah (Jurnal Manajerial, 2023)
Background – PT Garuda Indonesia (Persero) Tbk has been facing financial distress for the last five years. This is indicated by a significant loss in the amount of annual income. The revenue from operational activities has not been able to provide a profit for the company because of the high operating expenses that must be incurred. Aim – This study aims to find out how PT Garuda Indonesia (Persero) Tbk overcomes the current financial distress through the implementation of a retrenchment strategy. Design / methodology / approach – This study uses a case study method by analyzing sources from the implementation of the retrenchment strategy at PT Garuda Indonesia. The type of data used is secondary data in the form of annual reports and financial statements of the company which is analyzed qualitatively. Findings – PT Garuda Indonesia is one of the airlines that implements a retrenchment strategy in overcoming the problem of financial distress to increase the company's profitability. The type of retrenchment strategy implemented is a turnaround strategy and a captive company strategy. Conclusion - The implementation of the turnaround strategy is realized through the contraction strategy, consolidation strategy, and outsourcing strategy. The implementation of the captive company strategy is realized through the sole supplier strategy, preferred provider strategy, and contract grower strategy. Research implication – The results of this research are expected to be a consideration for the management of other airlines that are facing similar financial distress so that the company can maximize revenue and maintain business continuity in the aviation industry. Limitations – The limitation of this study is that the analysis is only carried out on data sourced from documentation and literature related to the retrenchment strategy that has been implemented by PT Garuda Indonesia in overcoming the problem of financial distress